Absenteeism of diabetics to appointments with an endocrinologist and its relationship with access to health services - Marcelle Lemos Leal; Edson Theodoro dos Santos Neto; Eliana Zandonade; Thiago Dias Sarti; Nagela Valadão Cade (Hospital de Clínicas de Itajubá, 2022)
Objective: To analyze the association between absenteeism and access to specialized consultations for diabetics, in the Unified Health System (SUS) in Espírito Santo (ES). Methods: Cross-sectional study conducted using primary and secondary data with 472 diabetics ≥ 18 years old scheduled in consultation with endocrinologist in the System of Regulation Centers of ES. The variables of the dimensions of access - availability, financial viability, and acceptability - were used to estimate the association with absenteeism. Logistic regression was used for the crude and adjusted analyses. Results: An association was found between absenteeism of diabetics and the variables living less than 10 km from the provider (OR: 1.81; 95%CI: 1.16 - 2.82, p = 0.01), need for transportation (OR: 4.89; 95%CI: 2.54 - 9.42, p < 0.001), and having financial expenses to attend the appointment (OR: 2.06; 95%CI: 1.23 - 3.44; p = 0.01). Conclusion: The main barriers of access to health services that contribute to the high prevalence of absenteeism from appointments with endocrinologists can be understood as a proxy for the socioeconomic status of diabetics and show close relationship with the social determinants of health.